(untitled) (Horizontes de Enfermería, 2020)
This article describes a reality in the city of Esmeraldas (Ecuador) and refers to the activities of the state refinery and their consequences, mainly those related to damage to the health of the population through the emission of gass and metals that get directly to people. The main objective was to establish the serum levels of heavy metals (especially lead) in the blood of residents of “Vuelta Larga” sector of Esmeraldas province and thereby confirm or disprove the hypothesis of the pulling impact of the activities of the Esmeraldas refinery in the population. A methodology that is based on fieldwork with the directly affected population was used to carry out this study, through surveys and the analysis of the blood of the afflicted people with their corresponding chemical analysis in the laboratory. At the end of the work, it was obtained that 59.4% of the people investigated have lead levels above the norm. It is concluded then that the gas emissions by the state refinery directly affect the health of the inhabitants of the city of Esmeraldas.